2016
DOI: 10.5455/msm.2016.28.125-128
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Target Organ Diagnostic Approach in Seasonal Allergic Rhinitis: Nasal Smear Eosinophils

Abstract: Background:Allergic rhinitis (AR) related to local weeds pollen sensitization (Chenopodiaceous family) is the most common cause of respiratory allergy in Kuwait. Local nasal accumulation of different cells typical of allergic inflammation is responsible for clinical symptoms of AR. Although nasal smear for Eosinophils (NSE) is one of the earliest included valuable test in diagnosis of AR, with time is underestimated.Aim:Explore possible correlation of natural pollen allergen stimulation with appearance and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although the nasal smear has been proposed as a useful tool for the diagnosis of allergic rhinitis, no consensus exists 19 , 20 . The nasal smear test is inexpensive, rapid, non-invasive and simple, yielding information on both acute and chronic rhinosinusitis 16 , 19 , 21 , 22 . Bousquet et al 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the nasal smear has been proposed as a useful tool for the diagnosis of allergic rhinitis, no consensus exists 19 , 20 . The nasal smear test is inexpensive, rapid, non-invasive and simple, yielding information on both acute and chronic rhinosinusitis 16 , 19 , 21 , 22 . Bousquet et al 5 .…”
Section: Discussionmentioning
confidence: 99%
“…VP4 is the major outer capsid protein encoded by the GCRV-II segment 6 gene, and it is one of the signature proteins used to detect the presence of GCRV [ 4 , 5 ]. The clear understanding of the target organs and infection routes of virus invasion can effectively prevent and control the outbreak of virus-induced diseases [ 6 ]. Previous study has reported that GCRV-II can infect most tissues of grass carp, mainly affecting the brain (especially), heart, and eyes of grass carp, and establishing latent infection in the brain tissue [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…VP4 is the major outer capsid protein encoded by GCRV-II segment 6 gene, and is one of the signature proteins used to detect the presence of GCRV [4]. The clear understanding of the target organs and infection routes of virus invasion can effectively prevent and control the outbreak of virus-induced diseases [5]. Previous study has reported that GCRV-II can infect most tissues of grass carp, mainly affecting the brain (especially), heart, and eyes of grass carp, and establishing latent infection in the brain tissue [6].…”
Section: Introductionmentioning
confidence: 99%